Structure and prevalence of thyroid disease in athletes - Turova, E. A.; Tenyaev, E. A.; Golovach, A. V.; Artikulova, I. N. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to assess the structure and prevalence of diseases of the endocrine system in athletes based on the in-depth medical examination. Methods and structure of the study. The study involved an analysis of the medical records of the athletes who had undergone an in-depth medical examination on the basis of Branch 1 of the State Autonomous Healthcare Institution of Moscow Centre for Research and Practice in Medical Rehabilitation, Restorative and Sports Medicine of Moscow Healthcare Department. We analyzed the data from a random sample of medical records of 604 athletes engaged in 48 sports, who had undergone the in-depth medical examination in 2016-2018. We considered the data of sports history, anthropometric measurements, thyroid, abdominal, and pelvic ultrasonography, results of the clinical and biochemical surveys of athletes, hormonal blood spectrum rates (TSH, free T4, prolactin, testosterone, cortisol, TPO antibodies), data of the instrumental survey (ECG, impedance monitoring, echocardiography, cycle ergometer test, spirometry).